Delving into the Political Preferences of Youth in Merauke's Border Area, South Papua - Adam, Aenal Fuad; Haris, Umiyati; Rachmat Saputro, Eko (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
The study of young voters has become a topic of interest to various academics and a strategic issue in local political dynamics, especially in contesting the 2024 Merauke Regional Head Elections. This study analyzes the factors influencing young voters' preferences in determining their political choices. Using a quantitative approach with a survey method, this study involved 300 respondents from among young voters in Merauke Regency. Three main approaches in the study of voter behavior were used. Namely, the sociological, social-psychological, and rational choice theory approaches are used to understand the complexity of the factors that influence the electoral decisions of young voters. The results showed that the Joseph Gebze-Fauzun Hinayah pair received the highest support (46%) from young voters due to their combined bureaucratic and legislative experience. The Hendrikus Mahuze-H. Riduwan pair came second with 28% support, which shows the appeal of executive and technocratic experience in local government. Meanwhile, David Gepze and H. Kusmanto obtained 21% of the vote despite receiving support from the local political elite, indicating that the influence of traditional leaders and the political elite is no longer a dominant factor for young voters. These findings also show that young voters are more independent and rational in determining their political choices. The candidate's track record, leadership competence, and development vision and mission are more decisive factors than traditional factors such as ethnic affiliation or political elite recommendations. In addition, social media is the main source of political information for young voters, reinforcing the argument that digitalization has increased their political awareness. This study concludes that issue-based campaign strategies, policy transparency, and political communication through digital platforms are crucial factors in attracting the support of young voters in the contemporary political era.